2013
DOI: 10.1186/1742-2094-10-110
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of neuronal IL-1β in acquired brain lesions in a rat model of neonatal encephalopathy

Abstract: BackgroundInfection-inflammation combined with hypoxia-ischemia (HI) is the most prevalent pathological scenario involved in perinatal brain damage leading to life-long neurological disabilities. Following lipopolysaccharide (LPS) and/or HI aggression, different patterns of inflammatory responses have been uncovered according to the brain differentiation stage. In fact, LPS pre-exposure has been reported to aggravate HI brain lesions in post-natal day 1 (P1) and P7 rat models that are respectively equivalent -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(69 citation statements)
references
References 32 publications
5
63
1
Order By: Relevance
“…The latter three processes are similar to those recently identified using microarray analysis of gene expression in oculomotor and spinal motor neurons 81 , while elevations in inflammation-associated proteins, specifically those of the complement pathway, have been previously associated with human ALS 70, 8284 and ALS model systems 85, 86 . We detect elevations in several proteins of the complement pathway, confirming previously-described elevations of CSF C3 70,82 and providing new evidence for an increase in C5 (which is upregulated in animal models of ALS 85, 87 ) and C2, as well as decreased complement factor I. Our results support a role of elevated complement pathway activation as a contributing factor to motor neuron death and a potential therapeutic target.…”
Section: Discussionsupporting
confidence: 74%
“…The latter three processes are similar to those recently identified using microarray analysis of gene expression in oculomotor and spinal motor neurons 81 , while elevations in inflammation-associated proteins, specifically those of the complement pathway, have been previously associated with human ALS 70, 8284 and ALS model systems 85, 86 . We detect elevations in several proteins of the complement pathway, confirming previously-described elevations of CSF C3 70,82 and providing new evidence for an increase in C5 (which is upregulated in animal models of ALS 85, 87 ) and C2, as well as decreased complement factor I. Our results support a role of elevated complement pathway activation as a contributing factor to motor neuron death and a potential therapeutic target.…”
Section: Discussionsupporting
confidence: 74%
“…Using the same model of inflammatory‐sensitized HI, we previously showed that the IL‐1/TNF‐α/MMP‐9 inflammatory axis was upregulated from 4 h to 24 h post‐HI, and played a key role in LPS + HI‐induced brain injuries (Savard et al, 2015, 2013). Thus, in the present study, we tested the influence of HT on the expression of these key neurotoxic molecules.…”
Section: Resultsmentioning
confidence: 99%
“…We previously showed that IL‐1β played a key role: (i) in the early (4–24 h) LPS + HI‐induced neuroinflammatory response, and (ii) in generating both core and penumbra cerebral injuries of NE (Savard et al, 2015, 2013). In the present study, HT acted only on penumbra but not on core of LPS + HI‐induced brain lesions of term‐like newborns.…”
Section: Discussionmentioning
confidence: 99%
“…Rats were placed on their back, four paws in the air. The time to move from paws in the air to four paws on the ground was measured and the pups were classified as having an impaired righting reflex when the delay to achieve a full righting reflex was more than 1 s. In the Elevated Body Swing Test (EBST) P16 rats were held by the base of the tail head downwards during 20 s, as previously described [42,46]. The number of effective upswings (+90°) and the total number of upswing were compared between the S + PT + H and LPS + PT + H groups.…”
Section: Methodsmentioning
confidence: 99%